Social function reconstruction of Intellectual Property Rights (IPR) based on justice values - Mashdurohatun, Anis; Ul Haq, Hayyan; Zulhuda, Sonny (Faculty of Law, Universitas Islam Sultan Agung (UNISSULA), 2017)
The purpose of this study is to examine and to analyze the construction of social functions of Intellectual Property Rights. Furthermore, it is also intended to know the urgency of social functions of Intellectual Property Rights and to reconstruct the social function of Intellectual Property Rights based on the value of Justice. The method used was doctrinal and non doctrinal approach by using primary and secondary data source. Moreover, the data was analyzed by using analytical descriptive. The result of the research shows that, the construction of social function of IPR has not been in accordance with Pancasila justice value. The urgency of social functions of IPR is as a form of crystallization of communal, inclusive and religious values. While the reconstruction of the social function of IPR was based on the value of Justice, namely by harmonizing the principle of Corporate Social Responsibility with the crystallization of communal, inclusive and religious values in using the IPR products, especially for copyrights and patents.